Doped Perovskite Materials for Solid Oxide Fuel Cell (SOFC) Anodes and Electrochemical Oxygen Sensors - Penwell, William (Université d'Ottawa / University of Ottawa, 2014)
This work focused on the study of three independent projects involving perovskite oxide materials and their applications as solid oxide fuel cell (SOFC) anodes and electrochemical oxygen sensors. The underlying theme is the versatility and tune-ability of the perovskite structure. Reactivity and conductivity (ionic as well as electronic) are modified to optimize performance in a specific application. The effect of Ce doping on the structure and the conductivity of BaFeO3 perovskite materials is investigated and the resulting materials are applied as oxygen sensors. The new perovskite family, Ba1-xCexFeO3-δ (x=0, 0.01, 0.03, and 0.05), was prepared via a sol-gel method. Powder XRD indicates a hexagonal structure for BaFeO3 with a change to a cubic perovskite upon Cerium doping at the A site. The solubility limit of Ce at the A site was experimentally determined to be between 5-7 mol %. Bulk, electronic and ionic conductivities of BaFeO3-δ and Ba0.95Ce0.05FeO3-δ were measured in air at temperatures up to 1000˚C. Cerium doping increases the conductivity throughout the entire temperature range with a more pronounced effect at higher temperatures. At 800˚C the conductivity of Ba0.95Ce.05FeO3-δ reaches 3.3 S/cm. Pellets of Ba0.95Ce.05FeO3-δ were tested as gas sensors at 500 and 700˚C and show a linear, reproducible response to O2. Promising perovskite anodes have been tested in high sulfur fuel feeds. A series of perovskite solid oxide fuel cell (SOFC) anode materials: Sm0.95Ce0.05FeO3-δ, Sm0.95Ce0.05Fe0.97Ni0.03O3-δ and Sm0.95Ce0.05Fe0.97Co0.03O3-δ have been tested for sulfur tolerance at 500°C. The introduction of the extreme 5% H2S enhances the performance of these anodes, verified by EIS and CA experiments. Post mortem analyses indicate that the performance XII enhancement arises from the partial sulfidation of the anode, leading to the formation of FeS2, Sm3S4 and S on the perovskite surface. Testing in lower concentrations of sulfur, more common in sour fuels, 0.5% H2S, also enhances the performance of these materials. The SCF-Co anode shows promising stability and an increase in exchange current density, io, from 13.72 to 127.02 mA/cm2 when switching from H2 to 0.5% H2S/99.5% H2 fuel composition. Recovery tests performed on the SCF-Co anode conclude that the open cell voltage (OCV) and power density of these cells recover within 4 hours of H2S removal. We conclude that the formation of metal sulfide species is only partially reversible, yielding an anode material with an overall lower Rct upon switching back to pure H2. Combining their performance in sulfur containing fuels with their previously reported coke tolerance makes these perovskites especially attractive as low temperature SOFC anodes in sour fuels. A new perovskite family Ba1-xYxMoO3 (x=0-0.05) has been investigated in regards to electrical conductivity and performance as IT-SOFC anode materials for the oxidation of H2. Refinement of p-XRD spectra as well as SEM imaging conclude that the solubility limit of Y doping at the A site is 5 mol%, beyond which Y2O3 segregation occurs. The undoped BaMoO3 sample has a colossal room temperature conductivity of 2500 S/cm in dry H2. All materials maintain metallic conductivity in the temperature range of 25-1000°C with resistance increasing with Y doping. The Ba1-xYxMoO3 (x=0, 0.05) materials exhibit good performance as SOFC anode materials between 500-800°C, with Rct values at 500°C in dry H2 of 3.15 and 6.33 ohm*cm2 respectively. The catalytic performance of these perovskite anodes is directly related to electronic conductivity, as concluded from composite anode performance.
Keywords: perovskite; conductivity; solid oxide fuel cell; anode; oxygen sensor